Employability skills: Do Islamic banking graduates well-developed? - Mohd Khairy Kamarudin; Azwan Abdullah; Nor Azilawati Ahmad; Siti Syakirah Yusoh; Siti Fariha Muhamad; Mohammad Ismail (Intercontinental Management Research Review, 2015)
Islamic banking industry in Malaysia has been emerged since 1983 with the establishment Bank Islam Malaysia Berhad and the enactment legal framework, Islamic Banking Act 1983. However, Islamic banking sector still being overwhelmed with the issue of shortage of qualified and skilled staffs even though there are various higher education institutions that offer Islamic banking course. Therefore, this study aims to investigate the level of employability skills among Islamic banking graduates. This study indicates that the level of employability skills is moderately high. However, there is no significant difference mean of employability skills between gender, age, CGPA and highest education background. This study recommends that higher education institutions and employers should cooperate together to enhance graduates employability skills such as design the course structure, industry placement, problem solving of case study and the establishment of “mock bank”.